2018
DOI: 10.1111/os.12405
|View full text |Cite
|
Sign up to set email alerts
|

Management of Dumbbell and Paraspinal Tumors of the Thoracic Spine Using a Single‐stage Posterolateral Approach: Case Series

Abstract: This study investigated the surgical results of a single‐stage posterolateral approach with arc incision, unilateral laminectomy, and costotransversectomy for the management of dumbbell tumors and paraspinal tumors of the thoracic spine. From January 2010 to March 2017, 14 patients with dumbbell tumors or paraspinal tumors of the thoracic spine who underwent resection with single‐stage posterolateral approach were followed up and analyzed retrospectively. The operations were performed using a single‐stage post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Using the extensive posterolateral approach enabled us to achieve maximal tumor resection and spine instrumentation in a one-step procedure. Similar results were achieved in other recent clinical studies that addressed the posterolateral approach (6)(7)(8)(9)(10)(11)(12). Despite its relative invasiveness, we confirmed that such an approach is safe and predictable as it is more familiar to neurosurgeons than the transthoracic approach, that usually requires the assistance of thoracic surgeons as well.…”
Section: Discussionsupporting
confidence: 90%
“…Using the extensive posterolateral approach enabled us to achieve maximal tumor resection and spine instrumentation in a one-step procedure. Similar results were achieved in other recent clinical studies that addressed the posterolateral approach (6)(7)(8)(9)(10)(11)(12). Despite its relative invasiveness, we confirmed that such an approach is safe and predictable as it is more familiar to neurosurgeons than the transthoracic approach, that usually requires the assistance of thoracic surgeons as well.…”
Section: Discussionsupporting
confidence: 90%
“… 12 Rong et al reported a series of 14 patients undergoing posterolateral resections without instrumentation. 17 Mean operative time and estimated blood loss were comparable with Li et al (272 min and 529 ml, respectively); however, one patient had subtotal resection and recurrence of disease. Zairi et al reported a series of five dumbbell tumors with mean maximal dimension of 46 mm resected by a posterior‐only approach.…”
Section: Discussionsupporting
confidence: 72%
“…Li et al reported favorable operative time (222 min), blood loss (400 ml), length of stay (8 days) and reduced pulmonary complications versus a combined approach 12 . Rong et al reported a series of 14 patients undergoing posterolateral resections without instrumentation 17 . Mean operative time and estimated blood loss were comparable with Li et al (272 min and 529 ml, respectively); however, one patient had subtotal resection and recurrence of disease.…”
Section: Discussionmentioning
confidence: 89%
“…They reported that the mean intraoperative blood loss was 360 mL, and the mean duration of using a drainage tube was 3 days 15 . With the development of minimally invasive techniques and devices, new surgical approaches have been used to remove thoracic dumbbell tumors in one operation and reduce unnecessary iatrogenic injuries caused by combining approaches [16][17][18] . Tubular or expandable retractors in tubular spinal surgery can expose tumors by expanding muscles in a stepwise manner, which not only reduces muscle and ligament injuries but also addresses tumor tissue in the epidural space.…”
Section: Advantages Of Tubular Spine Surgery For Thoracic Dumbbell Tumorsmentioning
confidence: 99%